THE STRATEGIC CHOICES OF SERBIAN ENTREPRENEURS: ARE THEY ENTREPRENEURIALLY ORIENTED AND DO THEY DIFFER BY GENDER? - Stošić Panić, Danijela (Economic Annals, 2019)
This paper focuses on the strategic practice of Serbian entrepreneurs by addressing the issue of their entrepre-neurial orientation. Based on a sample of 101 respondents (randomly drawn from the Serbian Business Registers Agency’s database), the research tries to answer the question of whether Serbian entrepreneurs’ strategic choices in the fields of growth, innovation, and marketing are entrepre-neurially oriented. The paper also reports research on gender differences regarding these issues. The results suggest that Ser-bian entrepreneurs are entrepreneurially oriented when making decisions about growth, innovation, and marketing. Also, Serbian women entrepreneurs are less en-trepreneurially oriented than men when choosing growth strategies, but more entre-preneurially oriented in certain aspects of market orientation. No statistically impor-tant gender differences were found regard-ing innovation strategies.